Clinical Profile of Leprosy Patients in DMCH - Khatun, Masuda; Sayed, MM Abu; Sultana, Tahmina (Community Based Medical Journal, 2017)
Leprosy is a chronic granulomatous infectious disease caused by Mycobacterium leprae, primarily affecting the skin and peripheral nerves. To find out the clinical profile of leprosy patients the cross sectional observational type of study was carried out in outpatient Dept of Dermatology and Venereology at DMCH, Dhaka. Total 30 cases were included in this study. The mean age was found 28.7±11.3 years. Male were 21(70.0%) and female were 9(30.0%). It was observed that 10(33.3%) patients were diagnosed as having borderline tuberculoid, 5(16.7%) as tuberculoid, 1(3.3%) as borderline, 6(20.0%) as borderline lepromatous and 8(26.7%) as lepromatous. Eighteen (60.0%) patients had mutibacillary and 12(40.0%) had paucibacillary. 28(93.3%) patients had hypopigmented, 27(90.0%) had marked anaesthesia, 26(86.7%) had macule & patch, 18(60.0%) had obvious margin and 9(30.0%) had plaque. Majority patients had symptoms during 6 months to 1 year. Common clinical manifestations of leprosy were obvious margin, hypopigmented, marked anaesthesia, macule and ear lobe enlargement. CBMJ 2017 January: Vol. 06 No. 01 P: 03-07